Need to Perform Rehabilitation Exercises at Home by Parents of Children with Neurological Diseases to Maintain Performance During COVID-19 Lockdown - Shamsoddini, Alireza; Bazgir, Behzad; Dalvan, Hamid (Iranian Journal of Child Neurology, 2021)
With the outbreak of the novel pandemic coronavirus disease 2019 (COVID-19) worldwide, many pediatric rehabilitation clinics have closed to support social &physical distancing and therapist like other people are staying in their homes. There is common concern of parents and caregivers that how and with which quality children’s rehabilitation exercises should be proceed. Most children with neurological diseases have problems such as muscle spasticity, range of motion limitation, muscle shortening, balance loss, mobility and movement impairment. The aim of this research was to summarize the necessaries of home based rehabilitation exercises program during quarantine period.